A hybrid risk-based approach for maritime applications: The case of ballast tank maintenance. Issue 6 (18th August 2017) - Gul, Muhammet; Celik, Erkan; Akyuz, Emre
ABSTRACT: Risk assessment is vital for cost-effective ship management in maritime industry since numerous maritime activities pose potential hazards according to the human causalities. Therefore, safety practitioners attempt to offer proactive approaches to mitigate risk as much as possible. In this context, this article presents a hybrid risk-based approach for maritime industry by adopting Fuzzy Analytic Hierarchy Process (FAHP) with fuzzy VIKOR (FVIKOR) methods under Fine-Kinney approach. To illustrate the hybrid risk-based approach, ballast tank maintenance process is handled since there are various hazards causing fatalities, severe injuries, and illness during ballast tank maintenance procedure than any other type of shipboard work. An extensive risk analysis is performed to enhance environment safety and operational reliability in maritime industry. Besides its theoretical contribution, the outcomes of the paper contribute to improve overall safety level of ship by considering potential hazards in risk management.